Effect of a Colombian isolate of bean southern mosaic virus on selected yield components of Phaseolus vulgaris - Morales, Francisco José; Castaño, M. (Scientific Societies, 1985)
The number and weight of seeds produced per plant were significantly (P = 0.01) reduced, 47.5 and 56.3%, respectively, in Diacol-Calima bean (Phaseolus vulgaris) plants infected with bean southern mosaic virus (BSMV). The number of pods per plant, on the contrary, was often higher in systemically infected plants than in uninoculated controls. An average of 17.4% of the pods produced by the BSMV-infected plants, however, did not produce seed. The virus was transmitted in 11.1% of the mature seeds produced by the BSMV-inoculated Diacol-Calima plants.